Differentiating the quality of friendships among students from other regions and local students based on multicultural personality - Vania Jacinda Anggawira; Setiasih (Jurnal Psikologi Tabularasa, 2025)
Indonesia is a country rich in diverse cultures, ethnicities, races, and religions. Migration for educational purposes is a common phenomenon, with many young people pursuing higher education in different regions. This quantitative study investigates differences in the quality of friendships between migrant and non-migrant university students, examined through the lens of multicultural personality. Participants were 184 active students at the University of Surabaya, aged 18–25, selected through purposive sampling. Data were collected using the Multicultural Personality Questionnaire–Short Form (MPQ-SF), the McGill Friendship Questionnaire–Friend’s Functions (MFQ-FF), and several open-ended questions developed by the researchers. Data analysis used ANCOVA and independent t-tests via SPSS. The results showed that multicultural personality significantly influenced friendship quality, but there were no significant differences in either friendship quality or multicultural personality between migrant and non-migrant students. Open-ended responses revealed that students choose friends based on shared tasks, hobbies, and personal traits rather than migration status. These findings suggest the need to consider other influencing factors and expand future research to diverse university settings to better understand student friendship dynamics.